Stained glass work, Archangel Michael - Ghosh, Ayan (2023)
A stained glass panel with a winged figure of the Archangel Michael wearing a cross on a tiara and pendant. Michael is an archangel in Judaism, Christianity, Islam, and the Baha'i faith. Michael is represented as a warrior: he is shown with a sword, in combat with or triumph over a dragon, from the story in the Book of Revelation.